MENINGKATKAN KINERJA PEMASARAN PERBANKAN UMUM NASIONAL - Syahril Yoserizal (JURNAL LENTERA BISNIS, 2015)
The purpose of this study was to determine and analyze the influence of good corporate governance on competitive advantage. To know and analyze the influence of information technology on competitive advantage. To know and analyze the influence of HR competencies on competitive advantage. To know and analyze the influence of good corporate governance, information technology, human resources competencies together on competitive advantage. To know and analyze the influence of good corporate governance on marketing performance. To know and analyze the influence of information technology on performance marketing. To know and analyze the influence of the performance of HR competencies on marketing. To know and analyze the influence of competitive advantage on marketing performance. To know and analyze the influence of good corporate governance, information technology, human resource competencies and competitive advantages together on marketing performance.The method used in this research is descriptive survey and explanatory survey with a sample size of 320 respondents, data analysis method used is SEM (Structural Equation Modeling). Based on the results of the study, the findings obtained of followed good corporate governance proved positively and significantly influenced on competitive advantage. Information technology proved positively and significantly influenced on competitive advantage. HR competencies positively and significantly influenced on competitive advantage. Good corporate governance, information technology and human resource competency together proved positively and significantly influenced on competitive advantage. However, partially, the most dominant influence was information technology competitive advantage. Good corporate governance proved positively and significantly influenced on the performance of marketing. Information technology proved positively and significantly influenced on the performance of marketing. HR competencies proved positive and significant impact on the performance of marketing. Good corporate governance, information technology, human resource competencies and competitive advantages together proved positively and significantly influenced on the performance of marketing. However, partially, was the most dominant influence on the competitive advantage of marketing performance. Keywords : Good Corporate Governance, Information Technology, Human Resources Competence, Competitive Advantage, Performance Marketing